Examination of the Relationship between Self-Compassion Levels of Preschool Period Children’s Mothers and Children’s Loneliness - Hülya Ogelman; İlkay Göktaş; Döne Kahveci (International Journal of Contemporary Educational Research, 2025)
Purpose of the research is to examine the predictive effect of self-compassion levels of preschool period children’s mothers over children’s loneliness levels.  The research was conducted with 196 children, between the ages of 60-72 months and who are attending preschool education in a metropolis in the South-eastern Anatolia Region, and their mothers.The relational survey method was used in the research. The Personal Information Form, Self-Compassion Scale and Loneliness Scale were adapted in the research.According to the research results; there is a negative, high level and significant relationship between self-compassion, self-kindness and awareness of sharing levels of mothers and loneliness levels of preschool period children. There is a positive, high level and significant relationship between self-judgement, isolation and over-identification levels of mothers and loneliness of children. Research findings indicate that mothers’ self-compassion is associated to and predicts loneliness of preschool period children. In light of the information in the literature, results of this study can be interpreted as the mother's self-compassion towards herself may reduce the child's level of loneliness by positively affecting her relationship with her child.